Proceedings of 2017 Chinese Intelligent Automation Conference - Deng, Zhidong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The proceedings present selected research papers from the CIAC'17, held in Tianjin, China. The topics include adaptive control, fuzzy control, neural network based control, knowledge based control, hybrid intelligent control, learning control, evolutionary mechanism based control, multi-sensor integration, failure diagnosis, reconfigurable control, and etc. Engineers and researchers from academia, industry, and government can gain valuable insights into solutions combining ideas from multiple disciplines in the field of intelligent automation.
Design of a Simulation System for Cross - eye Dynamic Jamming -- Design and production of a 3D printing robot hand with three underactuated fingers -- Dynamics control and Simulation of two DOF robot -- A New Tuning Approach to Second-order Acti- ve Disturbance Rejection Control -- RBF Based Integrated ADRC Controller for a Ship Dynamic Positioning System -- Research on Cross Platform Model Display Technology of BIM.
Keywords: Control engineering; Robotics; Automation; Computational intelligence; Control, Robotics, Automation; Computational Intelligence; Control and Systems Theory